Peran Mindset terhadap Resiliensi Keluarga pada Dewasa Awal - O. Irene Prameswari Edwina; Tessalonika Sembiring (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2021)
This study aims to examine the role of mindset on family resilience. This study used quantitative approach with correlational design. The participants were 275 adolescents. The mindset instrument was based in Dweck theory (20 items), while family resilience was measured using modification of Walsh Family Resilience Questionnaire (35 items). The data was analyzed using simple linear regression. The results show that the family resilience was predicted by mindset for 37.10%. The higher growth mindset, the higher the family resilience. Future research can explore other factors influencing family resilience formation and how family develop growth mindset.